2010
DOI: 10.1037/a0022079
|View full text |Cite
|
Sign up to set email alerts
|

Client attachment to therapist: Relation to client personality and symptomatology, and their contributions to the therapeutic alliance.

Abstract: This study examined the relation of client attachment to the therapist to diverse facets of the therapeutic alliance, client personality, and psychopathological symptoms, as well as the relative importance of therapeutic attachments, personality, and symptomatology in predicting the alliance. Eighty clients in ongoing therapy completed measures of client attachment to therapist (CATS), personality (6FPQ), psychopathological symptoms (BSI), and therapeutic alliance (WAI-Short, CALPAS, HAQ). Secure and Avoidant-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 78 publications
(89 reference statements)
4
43
1
3
Order By: Relevance
“…However, studies that have differentiated between the two types of insecure attachment, have generally found a lack of association between anxious attachment and the therapeutic alliance. For example, one study (Bachelor et al, 2010) examined the effect of clients' anxious and avoidant attachment on the therapeutic alliance among 80 individuals in therapy and found that, although avoidant attachment was associated with lower level of alliance, anxious attachment was not a significant predictor. Thus, there seems to be pattern that anxious attachment is not predictive the therapeutic alliance in individual and couple therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies that have differentiated between the two types of insecure attachment, have generally found a lack of association between anxious attachment and the therapeutic alliance. For example, one study (Bachelor et al, 2010) examined the effect of clients' anxious and avoidant attachment on the therapeutic alliance among 80 individuals in therapy and found that, although avoidant attachment was associated with lower level of alliance, anxious attachment was not a significant predictor. Thus, there seems to be pattern that anxious attachment is not predictive the therapeutic alliance in individual and couple therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Asimismo, se evaluó el apego en las relaciones en general y no el apego específico con el terapeuta debido a que los instrumentos que evalúan este último han mostrado compartir una gran variancia con herramientas que miden la alianza terapéutica, mostrando no ser constructos significativamente diferentes (Bachelor et al, 2010).…”
Section: Materialesunclassified
“…Igualmente se ha informado que una menor severidad sintomática se asocia con un mayor reporte de apego seguro (Smith et al, 2010) y que más sintomatología se relacionó con apego ansioso. Las inconsistencias descritas en la asociación entre apego ansioso o evitativo y la alianza podrían deberse a la influencia de terceras variables (Bachelor et al, 2010), siendo la mejoría/ empeoramiento sintomático una de ellas.…”
Section: Procedimientounclassified
See 1 more Smart Citation
“…Secure attachment to the therapist has been strongly, positively correlated with the therapeutic alliance (Bachelor, Meunier, Laverdiére, & Gamache, 2010;Goldman & Anderson, 2007;Mallinckrodt, Gantt, & Coble, 1995;Mallinckrodt, King, & Coble, 1998;Mallinckrodt, Porter, & Kivlighan, 2005;Satterfield & Lyddon, 1998), which in turn is a good predictor of successful therapeutic outcome (e.g., Horvath, Del Re, Flückiger, & Symonds, 2011;Horvath & Luborsky, 1993) accounting for, on average, about a quarter of the variance (Horvath & Symonds, 1991). Individuals with fearful-avoidant attachment styles tend to have the lowest therapeutic alliance ratings (Eames & Roth, 2000;Satterfiled, & Lydodon, 1998).…”
Section: Introductionmentioning
confidence: 99%